Learning Text Data Security in Documents Using McEliece's Algorithm - Sinar Sinurat; Edward R Siagian (Sean Institute, 2022)
Computer Assisted Instruction (CAI) is a very interesting computer-based learning media and is able to increase students' learning motivation. One model of CAI is a tutorial in which the delivery of material is carried out in a tutorial manner, as a tutorial is done by a teacher or instructor. The development of this design idea is based on how to design learning software for the McEliece cryptographic algorithm using the Computer Assisted Instruction (CAI) tutorial model by displaying the key formation process, the encryption process and the decryption process in the McEliece cryptographic algorithm, and including the McEliece cryptographic algorithm as material in learning applications. . The results of this study show that the McEliece cryptographic algorithm learning software is designed using the Computer Assisted Instruction (CAI) tutorial model and is useful for showing every step and result of the key formation process, the encryption process and the decryption process contained in the McEliece cryptographic algorithm, so that can help understand or learn work procedures or algorithms from the cryptography.